PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA PERKOSAAN STUDI PUTUSAN NOMOR 6/PID.SUSANAK/2020/PN.SIM - Yosua Martin Cendikia (Fakultas Hukum Universitas Tarumanagara, 2021)
Children are a mandate and gift from God Almighty, which is inherent in the dignity and worth as a whole human being. Child protection is the embodiment of justice in a society, thus child protection is sought in various fields of state and social life. One of the cases in the crime of rape where the victim is a girl aged 6 (six) years. This girl was raped and the perpetrator was sentenced to Article 81 paragraph (1) in conjunction with Article 76 d of Government Regulation in Lieu of Law No. RI. 1 of 2016 concerning the second amendment to the Republic of Indonesia Law No. 23 of 2002 concerning child protection which has been stipulated as Law no. 17 of 2016 which is punishable by a minimum imprisonment of 5 (five) years and a maximum of 15 (fifteen) years and a maximum fine of Rp. 5,000,000,000.00 (five billion rupiah). The article contains norms in the form of minimum and maximum words in the imposition of sanctions. Judges should decide based on the limits of the minimum and maximum in the norm. However, in this decision the judge determined differently where he was sentenced to 4 (four) years and Job Training for 3 (three) months at the Simalungun Regency Social Service. The application of appropriate sanctions in the decision of the Simalungun District Court Number 6/Pid.Sus-Anak/2020/PN. Sim is at least 5 years old.